PENGEMBANGAN LKS BERBASIS GUIDED DISCOVERY (PENEMUAN TERBIMBING) PADA POKOK BAHASAN BANGUN DATAR SEGI EMPAT KELAS VII SEMESTER 2 MTs LUNTO KOTA SAWAHLUNTO - SASMI, FUARA DILA (Pendidikan Matematika, 2014)
The background of this research is base on book activity (LKS) that used by theteacher still low in guiding low in guiding students to kind the concept ok math.Students is still low to understandmaterial about quadrilateral plane. It needs todevelop book activity (LKS) which can guide studentsdireetly and actively in kindingthe concept of learning. The purpose of this research is developing book activity(LKS) base on guided diacovery in validly and practicaly in quadrilateral planesubjeer. In designing this research, the researcher used four-D as modeldevelopment. There are four steps was done. Those are definision, designing,developing, and disseminate. The validator of this research arecectutes and teachers.The result of this research showed that book activity (LKS) base on guided discoveryin quadrilateral plane subject was valid and practice base on category.